Selection of Proper Potting Mixture for Root Trainer of Eucalyptus Hybrid - Shrivastava, Rajesh; Nanhorya, Rajesh; Upadhyaya, J. K. (Indian Forester, 1998)
The selection of proper potting mixture for Eucalyptus hybrid seedlings was carried out with various combinations of compost, soil, sand, coal pebbles, Teak seed husk, rice husk and saw dust. Seedlings height and root collar development were observed. The best results were obtained for potting mixture of compost, sand and soil in ratio 2 : 1 : 2.